Taxonomic determination of the cryptogenic red alga, Chondria tumulosa sp. nov., (Rhodomelaceae, Rhodophyta) from Papahānaumokuākea Marine National Monument, Hawai'i, USA: A new species displaying invasive characteristics. - Alison R Sherwood; John M Huisman; Monica O Paiano; Taylor M Williams; Randall K Kosaki; Celia M Smith; Louise Giuseffi; Heather L Spalding (PLoS ONE, 2020)
Survey cruises by the National Oceanic and Atmospheric Administration (NOAA) in 2016 and 2019 yielded specimens of an undetermined red alga that rapidly attained alarming levels of benthic coverage at Pearl and Hermes Atoll, Papahānaumokuākea Marine National Monument, Hawai'i. By 2019 the seaweed had covered large expanses on the northeast side of the atoll with mat-like, extensive growth of entangled thalli. Specimens were analyzed using light microscopy and molecular analysis, and were compared to morphological descriptions in the literature for closely related taxa. Light microscopy demonstrated that the specimens likely belonged to the rhodomelacean genus Chondria, yet comparisons to taxonomic literature revealed no morphological match. DNA sequence analyses of the mitochondrial COI barcode marker, the plastidial rbcL gene, and the nuclear SSU gene confirmed its genus-level placement and demonstrated that this alga was unique compared to all other available sequences. Based on these data, this cryptogenic seaweed is here proposed as a new species: Chondria tumulosa A.R.Sherwood & J.M.Huisman sp. nov. Chondria tumulosa is distinct from all other species of Chondria based on its large, robust thalli, a mat-forming tendency, large axial diameter in mature branches (which decreases in diameter with subsequent orders of branching), terete axes, and bluntly rounded apices. Although C. tumulosa does not meet the criteria for the definition of an invasive species given that it has not been confirmed as introduced to Pearl and Hermes Atoll, this seaweed is not closely related to any known Hawaiian native species and is of particular concern given its sudden appearance and rapid increase in abundance in the Papahānaumokuākea Marine National Monument; an uninhabited, remote, and pristine island chain to the northwest of the Main Hawaiian Islands.